A review of exercise as an intervention for reducing the risk of gestational diabetes between the years 2002-2021 - D'Orsi, Amanda (Kansas State University, 2021)
Introduction: Gestational diabetes is a common maternal complication, affecting 6-9% of pregnant women, that has increased in incidence in recent years coinciding with the increase in Type 2 diabetes. The American College of Obstetrics and Gynecology, the Academy of Nutrition and Dietetics and The Dietary Guidelines for Americans all recommend that pregnant women exercise a minimum of 150 minutes weekly to help promote maternal health and reduce risk of gestational diabetes. Randomized controlled trials have had conflicting results on the efficacy of exercise as an intervention to reduce the risk gestational diabetes. The purpose of this literature review was to evaluate if exercise during pregnancy is an appropriate intervention which could aid in reducing the risk of gestational diabetes. Method: A PubMed search of the MeSH terms exercise, and diabetes, gestational was completed. The initial search yielded 809 results. Next, the filters of randomized controlled trials, published between 2002-2021, the year the American College of Obstetrics and Gynecology changed their exercise guidelines, were applied which reduced the finding to 161 results. The 161 remaining studies were reviewed by title and abstract for relevance to the literature review. Studies were excluded for focusing on postpartum exercise, already onset gestational diabetes or a focusing on other maternal complications. The final selection for this review was 19 randomized controlled trials. Conclusion: There are many potential benefits, and limited risks without contradictions, of exercise during pregnancy. However, there is not a clear evidence available to support exercise during pregnancy as a preventive measure for gestational diabetes. Many studies failed to promote adherence to the exercise intervention. Additionally, exercise recommendations during child bearing years may be more appropriate to reduce of risk of gestational diabetes prior to pregnancy. More research should be completed focusing on a consistent exercise prescription to help substantiate the current recommendations.
Keywords: Prenatal exercise; Gestational diabetes; Pregnancy